Fortification of Civil-Military Cooperation Through Utilization of Geospatial Intelligence Concepts in Dealing with Armed Criminal Groups in Papua - Siswoputro, Suspada; Suseto, Buddy; Widjayanto, Joni; Prakoso, Lukman Yudho (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Acts of violence in Papua tend to increase and still occur today, although since 2001 the Indonesian government has attempted to implement a special autonomy policy. This research aims to find out why violence continues to occur even though development efforts are quite intensive. The special conditions in Papua require new alternatives to solving problems by utilizing the geospatial intelligence concept. This research was conducted using interpretive analytical-qualitative methods in Jakarta and Papua from January 2022 to October 2023. This research finds that there is a close relationship between topographic conditions with high levels of violence in Papua. This research shows the need to develop appropriate steps based on the principle of counterinsurgency operation, namely information about the population and unity of efforts through several steps. First by improving the legal status of Armed Criminal Groups, followed by fortifying cooperation between several related institutions, both civil and military, and supported by the use of advanced technology. So that these steps can produce accurate and comprehensive information that is very useful for the government or military command to be able to develop appropriate strategies to reduce the violence rate. Accurate and comprehensive information will make it easier to prepare strategic planning for military operations that are more effective, efficient, and with minimal casualties.